The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1123/japa.2013-0101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a One-Year Home-Based Case Management Intervention on Falls in Older People: A Randomized Controlled Trial

Abstract: This home-based case management intervention was not able to prevent falls or injurious falls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(60 citation statements)
references
References 24 publications
(43 reference statements)
2
58
0
Order By: Relevance
“…In fact, the control group reported fewer fall incidents. This is in line with another Swedish study of home-based fall prevention where the percentage of fallers and median of falls was higher in the intervention group, although not significant (15).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In fact, the control group reported fewer fall incidents. This is in line with another Swedish study of home-based fall prevention where the percentage of fallers and median of falls was higher in the intervention group, although not significant (15).…”
Section: Discussionsupporting
confidence: 91%
“…The dropout rate of approximately one in five is acceptable considering the high mean age and the frailty of the study population and is in line with dropout rates found in a similar study . In order to control not only the main outcome, days with falls, but also the intervention adherence of exercise and walks the participants were asked to report and submit these data for the entire study period, up to 12 months.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Eleven studies had a health promoting approach. Five of these studies focused on promoting general health (interventions which in addition to focusing on functional status also focused on health-related quality of life and/or social support aspects) [8,18,36,43,44], four promoted exercising [48][49][50]56], and two focused on promoting mental wellbeing [16,45]. The four remaining studies focused on preventing disability [46,[51][52][53].…”
Section: Overview Of Original Studiesmentioning
confidence: 99%
“…This study was developed in accordance with the Medical Research Council's framework on developing and evaluating randomised control trials for complex healthcare interventions (Medical Research Council, 2000). Details of the development of the case management intervention and pilot testing of the trial have been published elsewhere (Kristensson et al 2010) as have those on intervention effects on healthcare utilisation, costs and falls (Olsson Moller et al 2014, Sandberg et al 2015a.…”
Section: Developmentmentioning
confidence: 99%